2019
DOI: 10.1039/c9nr00498j
|View full text |Cite
|
Sign up to set email alerts
|

A biomimetic magnetosome: formation of iron oxide within carboxylic acid terminated polymersomes

Abstract: Bioinspired macromolecules can aid nucleation and crystallisation of minerals by mirroring processes observed in nature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…There are very few manuscripts regarding magnetoliposomes containing BMNPs. In fact, only magnetoliposomes containing Mms6-mediated BMNPs have been described so far, and their production is intended for magnetic resonance imaging [28][29][30]. Therefore, to our understanding, this is the first attempt to produce magnetoliposomes containing MamC-mediated BMNPs for a directed delivery of oxaliplatin, and it is also one of the first tryout for the local delivery of this drug, which may be of potential interest to locally treat CRC.…”
Section: Introductionmentioning
confidence: 99%
“…There are very few manuscripts regarding magnetoliposomes containing BMNPs. In fact, only magnetoliposomes containing Mms6-mediated BMNPs have been described so far, and their production is intended for magnetic resonance imaging [28][29][30]. Therefore, to our understanding, this is the first attempt to produce magnetoliposomes containing MamC-mediated BMNPs for a directed delivery of oxaliplatin, and it is also one of the first tryout for the local delivery of this drug, which may be of potential interest to locally treat CRC.…”
Section: Introductionmentioning
confidence: 99%
“…In another paper, Bain et al (2019) documented a combination of 2 diblock co-polymers made up from PEG and carboxylic acid terminated poly (2-methacryloxyethyl phosphorylcholine) (PMPC) (called polymersome). PMM28 magneto-polymersomes (PMM28Fe) showed a 6 ° C increase in temperature during magnetic hyperthermia in vitro, resulting in an intrinsic loss power (ILP) of 3.7 nHm 2 kg −1 that offers the added potential for further tuning and functionalization for imaging and drug delivery purposes [ 243 ]. Aouidat et al (2019) reported a new Gd(III)–biopolymer—Au(III) complex synthesis that acts as a key component of Gold core-shell nanoparticles (Gd(@AuNPs).…”
Section: Stimuli-responsive Polymeric Nanocarriers For Bioimagingmentioning
confidence: 99%
“…However, one possible solution to this issue is based on the clustering of many superparamagnetic nanocrystals into larger nanoparticles that preserve the superparamagnetic properties, while possessing enhanced magnetic moment that is suitable for effective spatial guidance of the particles in suspension. Therefore, different approaches of superparamagnetic nanoparticle clustering have been proposed in the last two decades, including: one-pot nanoparticle cluster synthesis method, solvothermal methods, chemical cross-linking of nanoparticles in the cluster, preparation of composite nanoparticle clusters with polymers, and emulsion/evaporation-based clustering of hydrophobic nanoparticles, among other strategies ( Figure 6 ) [ 29 , 41 , 42 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 ]. Krasia-Christoforou et al has recently presented an elegant topical review on magnetic nanoparticle clustering that is available for further reading [ 88 ].…”
Section: Natural and Bioinspired Synthetic Approaches To Form Magnetic Nanochainsmentioning
confidence: 99%